Mythopoetic and Realistic Image of the Native Land in the Works of Modern Writers - lshatovna Nureeva, Gulshat; Faridovna Kayumova, Gelyusya; Ihsanovna Mingazova, Liailia; Victorovich Petrov, Alexander (International Journal of Criminology and Sociology, 2022)
The article explores the specifics of the embodiment of the image of the native land in the works of modern writers. After the years of Soviet power, when a person was evaluated as a cog, nature as a source of resources, society overestimates the value system. Quite well-known works appear condemning the rejection of man as a person, works of an ecological nature. In this article, a rethinking of attitude to nature, to the native land is considered through the prism of a number of works by venerable writers about the native land, more often - about the native village. Distinctive features of the perception of the native land in these works is the personally significant perception of the homeland, its understanding as part of itself, its past, present and future, in contrast to Soviet literature, in which the narrator was aimed at perceiving the homeland in the present and illusory beautiful future. Sources are the stories of M. Galiev, G. Gilmanov, M. Vali-Bardzhily. The creativity of each of these authors was considered to varying degrees by scientists from the point of view of aesthetic value, poetics, and problems. However, the native land was considered more as a subject of works, rather than an independent image, which is an indicator of the life values and philosophy of writers. In this article, using the works of these writers as an example, the depth of the image of the native land is shown, understanding it not only as nature or the place where you were born, but as a source of strength.